2020
DOI: 10.12691/jfnr-8-10-9
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Value, Energy and Nutrient Contents and Claims of Marketed Multi-grain Breads

Abstract: Cereals, mainly bread from plain wheat flour, are the staple food in Jordan. Leavened Arabic bread is the traditional consumed form. Bread is also produced in other forms by the addition of ingredients not present in the traditional Arabic bread. These forms of bread are associated with some nutrient content claims. This study aimed to compare the proximate analysis and energy of 16 multi-grain breads, in addition to white bread, and their declared nutrient content claims. The mean contributions of carbohydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The energy content of the bread samples in this study was comparable to the values reported by Refat et al. ( 2020 ). From these values, it implies that vegetable bread is capable of providing enough energy to satisfy the needs of consumers.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The energy content of the bread samples in this study was comparable to the values reported by Refat et al. ( 2020 ). From these values, it implies that vegetable bread is capable of providing enough energy to satisfy the needs of consumers.…”
Section: Resultssupporting
confidence: 91%
“…The calorific values of bread samples ranged from 1125.19 to 1332.73 kJ and were significantly different from one another both within and among the group of vegetable bread samples, with the lowest value found in moringa 7% bread and the highest value found in amaranth 5% bread. The energy content of the bread samples in this study was comparable to the values reported by Refat et al (2020). From these values, it implies that vegetable bread is capable of providing enough energy to satisfy the needs of consumers.…”
Section: Proximate Compositionsupporting
confidence: 85%
“…This is because dietary fibers may interfere with the development of the gluten network. Dietary fiber can interfere with gas bubble formation by weakening the gluten network and disrupting the starch–protein network, thereby connecting the bubble lamellae (Alkurd et al, 2020). The interactions between dietary fibers and gluten have been reported predominantly through hydrogen bonding, hydrophobic interactions, and physical interaction (competition for water and steric hindrance) (Zhou et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Bread, particularly white bread, is a staple and convenient food many people consume worldwide. It is energy‐dense (about 288.58 kcal/100 g) (Alkurd et al, 2020) rather than nutrient‐dense food as it is low in protein (8.6%–11.8%) and amino acid lysine (2.18 mg/g of protein) (Centenaro et al, 2007). The overconsumption of bread can also be related to the development of diet‐related noncommunicable diseases, for example, type 2 diabetes (Bautista‐Castaño & Serra‐Majem, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different replacement levels used to develop multigrain bread significantly affect its nutritional quality attributes (Mir et al, 2019). Different multigrain mixtures were prepared by researchers and replaced with different proportions of wheat flour (Alkurd et al, 2020). The replacement of wheat flour with different ratios of multigrain blend prepared by mixing oats, soya bean, flaxseed, fenugreek, and sesame seeds on nutritional properties of bread was studied by Indrani et al (2010).…”
Section: Nutritional Propertiesmentioning
confidence: 99%